The Routledge handbook of cultural landscape heritage in the Asia-Pacific - Kapila D. Silva; Taylor, Ken; Jones, David S. (Oxon : Routledge, 2023)
"The Routledge Handbook of Cultural Landscape Heritage in the Asia-Pacific revisits the use, growth, and potential of the cultural landscape methodology in the conservation and management of culture-nature heritage in the Asia-Pacific region."--
Keywords: Cultural property--Protection; Historic preservation